Optimization of the status of cell growth guided by an on-line biomass sensor for polymalic acid fermentation. (April 2019) - Zou, Xiang; Li, Tianfu; Zhang, Xiao; Li, Hongqing; Wang, Bochu
Graphical abstract: Highlights: The amount of viable cells was sensitive to regulation by available nitrogen. Cell morphology became looser and larger at the fermentation stage. A comparable fed-batch strategy was developed to balance cell growth and PMA biosynthesis. The maximum PMA yield was scaled up in a 50-L fermentor. Abstract: Polymalic acid (PMA) is a water-soluble biopolymer, composed of the monomer malic acid (MA), produced by Auerobasidium pullulans. In this study, an on-line biomass monitor was used to evaluate the status of viable biomass from seed culture to fermentation for PMA production. The amount of viable cells was sensitive to regulation by available nitrogen. From the exponential phase, cell morphology became looser and larger as demonstrated by the fc value and light microscopy. These findings were consistent with the average cell circumference, which increased from 10.8 ± 1.31 to 12.4 ± 1.90 μm. Under the optimized seed culture, a comparable fed-batch strategy was developed to balance cell growth and PMA biosynthesis in a 5-L fermentor, achieving PMA titers up to 128.3 ± 1.51 g/L with a corresponding yield of 0.54 g/g glucose. The process was further guided by the biomass sensor and scaled-up in a 50-L fermentor, producing 144.3 ± 1.8 g/L PMA (or 163.8 g/L malic acid after hydrolysis) with a maximum MA productivity and yield of 0.91 g/L h and 0.60 g/g, respectively. This study will helpful for understanding the relationship between cell growth and PMA biosynthesis and provided an operable fermentation process for large-scale PMA production.